Biocoagulant effectivity test in tempe wastewater treatment: the effect of biocoagulant type and dosage - Lia Cundari; Ade Tiara; Kha-Rizma Yudia Zannah (Institution for Industrial Research and Standardization of Industry - Padang, 2023)
Tempe is a popular Indonesian food enjoyed by many people. However, the production process generates a significant amount of liquid waste. Liquid waste treatment can be done through coagulation and floctuation processes with the help of coagulants. The purpose of this study was to determine the effect of the type and dose of biocoagulant on the turbidity and pH values of tempe wastewater The variations included the use of various biocoagulants (papaya seeds, tamarind seeds, and moringa seeds), biocoagulant doses (500, 1000, and 1500 mg/L) and variations in slow flocculation time (10, 15, 20, 15, 25, and 30 minutes). The analysis encompassed measurements of turbidity, pH, COD, BOD, and TSS. The research data is then validated in a certified laboratory. The results showed that the type of biocoagulant, dose of biocoagulant and stirring time would affect the turbidity value of tempe wastewater but did not significantly affect the pH value. The highest reduction in turbidity was 52.3 NTU with a percent decrease in turbidity of 96.2% at pH 4.145 using 500 mg/L tamarind seed biocoagulant and stirring time of 25 minutes. The results showed that only the BOD and TSS parameters met the tempe liquid waste quality standards, so that further processing was required, such as by adsorption and electrocoagulation.